The healing powers of herbs and spices : a complete guide to nature's most magical medicine - Orey, Cal, 1952- (Citadel Press, Kensington Publishing Corp., 2021)
Explores the many ways fresh herbs and dried spices can provide medicinal powers, home cures, weight loss benefits, and more.